Functional outcome of mild and moderate residual varus in posterior stabilized total knee arthroplasty in primary osteoarthritis knee: a prospective study - C., Bharath M.; Prakashappa, T. H.; B., Madhusudan; M., Nithin S. (International Journal of Research in Orthopaedics, 2022)
Background: Total knee arthroplasty (TKA) is one of the most commonly done orthopaedic surgical procedures for treating severe arthritis of the knee joint caused by osteoarthritis or inflammatory arthritis. The current clinical investigation, done at the Sanjay Gandhi Institute of Trauma and Orthopaedics in Bengaluru, provided the short-term functional result of mild and moderate residual varus in posterior stabilized TKA. The aim was to evaluate the efficacy of mild and moderate residual varus in total knee replacement for primary OA knee in terms of pain relief, range of motion and stability of the joint. Methods: 30 total knee replacements were performed. All patients were examined pre- and post-operatively using the knee society clinical and functional score. The average pre-op KSS knee score was 38.7, with a functional score of 23.3. The most common reason for TKR was osteoarthritis. The follow-up time ranged from 6 to 12 months. Results: By the knee society clinical, functional score method, 96.6% of our patients received an outstanding assessment after scoring 80 points or higher. The mean post-operative KSS knee score is 86.57, and the knee society functional score is 92. 92% of patients had little/no pain after surgery, and walking ability increased and was unlimited in 80% of patients. Conclusions: After a short term follow up of 1 year in a research population of 30 with pre-operative osteo arthritis of the knee, with post-operative mild to moderate varus alignment showed better clinical results.